Marginal taxation of labor income in Sweden from 1862 to 2010 - Gunnar Du Rietz; Dan Johansson; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2013)
This paper presents annual Swedish time series data on the top marginal tax wedge and marginal tax wedges on labor for a low, average and high income earner for the period 1862 to 2010. We identify four distinct periods separated by major tax reforms. The tax system can be depicted as proportional, with low tax wedges until World War II. Next follows a period featuring increasing tax wedges beginning in connection with World War II. During the third period, starting with the 1971 tax reform and continuing throughout the 1980s, the efforts to redistribute income culminated and tax wedges peaked. The high income earner started to pay the top marginal tax wedge which could be 90 percent. The main explanations for this development are temporary crises leading to permanent tax increases, expansion of the public sector and distributional ambitions, bracket-creep and the introduction of social security contributions paid by the employers. The 1990-1991 tax reform represents the beginning of a new and still continuing period with decreasing marginal tax wedges.
Keywords: H21; H31; N44; 330; Labor taxation; Marginal tax rate; Marginal tax wedge; Tax reforms